2013
DOI: 10.1111/phn.12079
|View full text |Cite
|
Sign up to set email alerts
|

A Rural African American Faith Community's Solutions to Depression Disparities

Abstract: Objective The aim of this study was to explore how a rural African American faith community would address depression within their congregations and the community as a whole. Design and Sample A qualitative, interpretive descriptive methodology was used. The sample included 24 participants representing pastors, parishioners interested in health, and African American men who had experienced symptoms of depression in a community in the Arkansas Delta. Measures The primary data sources for this qualitative res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…For example, Grothe began work on studying the validity of the BDI in low-income African Americans and found that the studies using the BDI-II included no more than 15% of African Americans in each sample (Grothe et al, 2005) which might make the identification and detection of depressive symptoms difficult to decipher. Additionally, the underestimation of rates of depression in African American communities resulting from selection bias in the main studies has contributed to the lack of understanding of the use of mental health services among people of African descent (Barnes, Keyes, & Bates, 2013; Bryant, Haynes, Kim Yeary, Greer-Williams, & Hartwig, 2014; Gary, Yarandi, et al, 2015). …”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…For example, Grothe began work on studying the validity of the BDI in low-income African Americans and found that the studies using the BDI-II included no more than 15% of African Americans in each sample (Grothe et al, 2005) which might make the identification and detection of depressive symptoms difficult to decipher. Additionally, the underestimation of rates of depression in African American communities resulting from selection bias in the main studies has contributed to the lack of understanding of the use of mental health services among people of African descent (Barnes, Keyes, & Bates, 2013; Bryant, Haynes, Kim Yeary, Greer-Williams, & Hartwig, 2014; Gary, Yarandi, et al, 2015). …”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…A parallel line of work is exploring ways that congregational leadership may develop programmatic strategies for the transmission of health-related messages emphasizing sexual health and regular health screening (Brown and Cowart 2018; Powell et al 2017; White et al 2020). Additionally, several studies have highlighted the mental health benefits that accrue to members of disadvantaged communities, often persons of color, who are able to access faith-based support systems (Bryant et al 2014; Bryant et al 2015; Taylor et al 2000; Williams et al 2014). Continuing the focus on aging populations, Krause and Hayward (2012) have provided evidence of positive associations between pastoral emotional support, beliefs in God's ability to alleviate personal burdens and a greater sense of hopefulness in late life.…”
Section: Literature and Hypothesesmentioning
confidence: 99%
“…The aim was to gain an understanding of rural African American community perspectives on depression and ideas for eliminating depression disparities among rural African Americans, as a basis for developing a faith-based depression intervention targeting individuals in the rural African American faith community. 33 The focus groups identified key aspects of an intervention to address depression. Major needs identified included needs for 1) tools to help parishioners manage their stress, 2) education for the faith community about how to recognize and seek help for depression, 3) confidentiality and privacy in seeking mental health services, 4) training of lay leaders in the church to be “depression experts,” and 5) finally, given the stigma associated with depression, use of a term such as stress or something less threatening rather than calling an intervention a “depression intervention.” Other studies have also found that African American populations described depression as “stress” or “a funk.” 3537 The focus group participants said that the intervention did not need to be different for men and women, but should be delivered separately for the two groups, both to provide opportunities for male bonding and to address gender-specific issues.…”
Section: Formative Researchmentioning
confidence: 99%
“…45 These three factors interact to assist individuals within social networks to improve their coping resources and health behaviors. 33 The theory provides a framework for harnessing the power of social relationships to increase coping self-efficacy, which in turn should reduce perceived stress, psychological distress, and depression.…”
Section: Formative Researchmentioning
confidence: 99%